Differential Gene Expression in the Heads of Behaviorally Divergent Culex pipiens Mosquitoes - Anna Noreuil; Megan L. Fritz (Insects, 2021)
Host preferences of Cx. pipiens, a bridge vector for West Nile virus to humans, have the potential to drive pathogen transmission dynamics. Yet much remains unknown about the extent of variation in these preferences and their molecular basis. We conducted host choice assays in a laboratory setting to quantify multi-day human and avian landing rates for Cx. pipiens females. Assayed populations originated from five above-ground and three below-ground breeding and overwintering habitats. All three below-ground populations were biased toward human landings, with rates of human landing ranging from 69–85%. Of the five above-ground populations, four had avian landing rates of >80%, while one landed on the avian host only 44% of the time. Overall response rates and willingness to alternate landing on the human and avian hosts across multiple days of testing also varied by population. For one human- and one avian-preferring population, we examined patterns of differential expression and splice site variation at genes expressed in female heads. We also compared gene expression and splice site variation within human-seeking females in either gravid or host-seeking physiological states to identify genes that may regulate blood feeding behaviors. Overall, we identified genes with metabolic and regulatory function that were differentially expressed in our comparison of gravid and host-seeking females. Differentially expressed genes in our comparison of avian- and human-seeking females were enriched for those involved in sensory perception. We conclude with a discussion of specific sensory genes and their potential influence on the divergent behaviors of avian- and human-seeking Cx. pipiens.